Perceived Pain in People Living with Amyotrophic Lateral Sclerosis—A Scoping Review - Debora Rosa; Laura Ingrande; Ilaria Marcomini; Andrea Poliani; Giulia Villa; Martina Sodano; Duilio Fiorenzo Manara (Nursing Reports)
(1) Background: Pain is a common symptom in patients with Amyotrophic Lateral Sclerosis (ALS). There are no evidence-based pharmacological treatments for pain in ALS; recommendations are based on guidelines for chronic non-oncological pain and clinical experience. The aim is to map the literature on how people with ALS experience pain, and how this affects their daily activities and social relationships. (2) Methods: This scoping review included studies concerning patients with spinal/bulbar ALS aged ≥ 18 years who experience pain, focusing on perception, characteristics, treatment, and impact on quality of life. Temporal and linguistic criteria were applied when searching the MEDLINE, CINAHL, and SCOPUS databases. (3) Results: The management of pain in these patients is complex and involves the use of anti-inflammatory drugs, analgesics, and opioids. Pain is associated with other conditions such as depression and anxiety, which contribute to a deterioration in the quality of life. Moreover, pain may also negatively influence patient compliance with prescribed treatment regimens and the quality of care they perceive themselves to be receiving. (4) Conclusions: It is of the most importance to identify effective ways to assess and treat this issue, with health care professionals taking an active role in this process.